Acute heart failure and cardiogenic shock: a multidisciplinary practical guidance - Mebazaa, A; Tolppanen, H; Mueller, C; Lassus, J; DiSomma, S; Baksyte, G; Cecconi, M; Choi, D J; Cohen Solal, A; Christ, M; Masip, J; Arrigo, M; et al. (Intensive care medicine, 2016)
PURPOSE: Acute heart failure (AHF) causes high burden of mortality, morbidity, and repeated hospitalizations worldwide. This guidance paper describes the tailored treatment approaches of different clinical scenarios of AHF and CS, focusing on the needs of professionals working in intensive care settings. RESULTS: Tissue congestion and hypoperfusion are the two leading mechanisms of end-organ injury and dysfunction, which are associated with worse outcome in AHF. Diagnosis of AHF is based on clinical assessment, measurement of natriuretic peptides, and imaging modalities. Simultaneously, emphasis should be given in rapidly identifying the underlying trigger of AHF and assessing severity of AHF, as well as in recognizing end-organ injuries. Early initiation of effective treatment is associated with superior outcomes. Oxygen, diuretics, and vasodilators are the key therapies for the initial treatment of AHF. In case of respiratory distress, non-invasive ventilation with pressure support should be promptly started. In patients with severe forms of AHF with cardiogenic shock (CS), inotropes are recommended to achieve hemodynamic stability and restore tissue perfusion. In refractory CS, when hemodynamic stabilization is not achieved, the use of mechanical support with assist devices should be considered early, before the development of irreversible end-organ injuries. CONCLUSION: A multidisciplinary approach along the entire patient journey from pre-hospital care to hospital discharge is needed to ensure early recognition, risk stratification, and the benefit of available therapies. Medical management should be planned according to the underlying mechanisms of various clinical scenarios of AHF.
Keywords: péče o pacienty v kritickém stavu; Acute Disease; Heart failure; směrnice pro lékařskou praxi jako téma; srdeční selhání; Shock, Cardiogenic; Emergency; lidé; Critical Care; kardiogenní šok; Practice Guidelines as Topic; Treatment; akutní nemoc; Humans; Heart Failure; Cardiogenic shock